Human Capital in the First 80 Years of the Republic: How Much Did America Owe the Rest of the World? - Gallman, Robert E. (American Economic Review, 1977)
The first thing to establish is the number of foreign-born persons who entered the United States and remained therein, during the first 80 years or so of American national history. Unfortunately, the evidence on this point is imperfect. We know that black Africans came to the United States as slaves, almost without exception, that the slave trade was officially closed in 1807, that while illegal importations continued down to the Civil War, the number of persons involved was probably relatively small, and that few American slaves were exported. Almost 19 percent of Americans were black in 1810. By 1860, the fraction had dropped to about 14 percent, reflecting the facts that black immigration had very nearly come to a halt, after 1807, while nonblack immigration had not. So far as I can tell, from the work of Philip Curtin and Robert Fogel and Stanley Engerman, between four-tenths and six-tenths of the slaves ever imported into the territory encompassed by the United States were imported in the years after the Revolution. That group represented an increment of between one-third and one-half to the pre-existing black population. The American black population, therefore, was not simply a heritage of American colonial history. When W. E. B. Du Bois mourned the missed opportunity of emancipation at the time of the Constitutional Convention, he perceived (among other things) the impact on American society of the subsequent expansion of the slave class by importation and the increasing scope of the violence that would be required to do away with slavery, a point to which I will return. The immigration of free men is no better (perhaps worse) recorded than the immigration of slaves, down to 1820. But the evidence suggests that it was a relatively unimportant component of the growth of the American population until the 1840's, when the great migrations of the Irish, Germans, and British began. Thus, in contrast to the migration of slaves, which took place chiefly in the first two and a half decades or so of the period between the Revolution and the Civil War, the migration of free men was concentrated in the decades of the 1840'sand 1850's. In 1850, about lOpercentof the free, white population was foreign born, while by 1860, the fraction had risen to about 13 percent.